The man in the iron mask - Dumas, Alexandre, 1802-1870 ([Boston, Mass] : Thomson Heinle, 2007)
Reunited thirty years after their earlier adventures, D'Artagnan and the Three Musketeers join forces once again, this time in a daring plot to replace the King of France with a mysterious look-alike! Follow their thrilling adventures as they free a royal prisoner from the Bastille--as they place him on the throne--and as they suffer the true king's revenge, in this, the last and most exciting tale of the Four Musketeers
Title from container
Keywords: Princes -- Fiction; France -- History -- Louis XIV, 1643-1715 -- Fiction